(untitled) (Journal of Applied Science and Engineering A, 2022)
Let V be the classical Volterra operator on L2(0, 1). The quadratic forms and their applications are used in many branches of mathematics. In this area of mathematics have studied many properties for concrete operator such as the numerical range. In recent year, the concept of Volterra operator has attached the serious attention of many researchers. In this paper, we compute the operator norm of self-commutators of V and its square. We also study the length of arc and the area of numerical range of V.